O016 Renal function at baseline and month 1 in the PROUD study, a pragmatic open label randomised trial of Truvada as Pre-Exposure Prophylaxis. (30th June 2016) - Reeves, Iain; White, Ellen; Brodnicki, Elizabeth; Dunn, David; McCormack, Sheena; Barber, Tristan; Sullivan, Ann; Lacey, Charles; Alexander, Hannah
Abstract : Background/introduction: Quarterly monitoring of creatinine is likely to be recommended by WHO for those on PrEP, even though there were no significant differences in creatinine in placebo-controlled trials. Establishing the appropriate level of monitoring of PrEP is important. Methods: PROUD is an open-label, randomised trial of Truvada as PrEP in MSM. HIV serology and serum creatinine was done at PrEP baseline ('start'). Clinics were advised to collect creatinine or urinary protein-creatinine ratio (UPCR) if there was ≥1+ protein on urinalysis at the month 1 visit (m1). Herewe present the renal monitoring results at "start" and m1 with eGFR (ml/min/1.73m 2 ) calculated by the CKD-EPI equation. Results: 445 (93%) of 481 had baseline creatinine, 13 (3%) had UPCR, and 23 (5%) neither. The median eGFR was 106. Only one was <60 (eGFR = 49), probably due to dietary creatinine supplementation. 260 (59%) of 443 had a m1 creatinine, creating 246 paired results. On average, eGFR was 1.50 lower at m1. Seven (4%) of 194 with eGFR >90 dropped 20%, one to 59. He stopped PrEP and did not attend thereafter. Of the 7, none had abnormal urinalysis; 4 had UPCR – all normal. 41 (79%) of 52 with eGFR 60–90 at baseline remained at this level, the remainder increased to >90. Discussion/conclusion: The mean change in eGFR at month 1 is not clinically significant. Excepting one individual who could not be further evaluated, there were no clinically meaningful changes at m1. Further work will explore the relationships between eGFR and proteinuria.